Analisis Manfaat Program AKLAM dalam Peningkatan Pemanfaatan Laboratorium Fisika - Muhammad Qaddafi; Santih Anggereni; Muh. Syihab Ikbal; Mukti Ali; Nur Ika Akbar (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2023)
This research is a Mixed Methods research with a concurrent triangulation research design, The objectives of this study are: 1) To find out the picture of the arrangement of school laboratory governance after the application of student laboratory work (AKLAM) of the Physics Education study program UIN Alauddin Makassar in the Takalar and Bulukumba areas ”; 2) To find out the description of the use of school laboratories after the application of student laboratory work (AKLAM) of the Physics Education study program UIN Alauddin Makassar in the Takalar and Bulukumba areas"; 3) To find out what contributions have been obtained by the school after the implementation of the Student Laboratory Work Application (AKLAM) of the physics education study program of UIN Alauddin Makassar in the Takalar and Bulukumba areas". Thefocus of this research is one Madrasah Aliyah and one junior high school usingquestionnaires in the form of checklist sheets and interview sheets, the results of the analysis obtained are: 1) for post-AKLAM governance there are two schools that are still sufficient in accordance with school laboratory standards and there is one school that is no longer in accordance with school laboratory standards; 2) for utilization post-AKLAM laboratory, namely the use of the laboratory as a practicum place is still maintained; 3) for the contribution obtained by each post-AKLAM school is very positive